An Evaluation of Clinical Assessment Tools for Menopausal Women with Emphasis on Psychological Dimensions (Homoeopathy for All, 2024)
Menopause is a natural biological  transition in a woman's life,  often accompanied by a range  of physical and psychological  symptoms. The assessment tools  under scrutiny encompass a wide  array of questionnaires, surveys,  and structured interviews designed  to gauge psychological symptoms  such as mood swings, depression,  anxiety, and overall quality of life  during the menopausal transition.  The study aims to identify and  analyze the effectiveness of these  tools in accurately capturing the  psychological aspects of menopause,  with the ultimate goal of enhancing  the quality of care and support  provided to menopausal women.
Keywords: Menopause; Climacteric age; Clinical assessment tools; Psychological dimension; Women's health; Mood swings